Análisis de los restos óseos recuperados en el rescate arqueológico del cementerio Central (Montevideo, Uruguay) - Rojo, Belén; Melgar, Macarena; Curbelo, Lucía; Figueiro, Gonzalo (Pontificia Universidad Católica del Perú, 2021)
In January 2019 there was a partial collapse of the «E» wing of the first body of funerary niches of the Central Cemetery of Montevideo, affecting 64 niches containing burials from the mid-nineteenth century to the present. The archaeological rescue work of the collapsed sector resulted in the recovery of intact or slightly altered funerary structures and in the extraction of displaced or isolated remains that were analyzed separately and are the object of this work. The remains were studied in order to determine the number of individuals, sex and age structure, and the effect of the collapse and the recovery methodology on the representation of bone elements. Three specific studies were carried out on subsets of the sample: taphonomy of adult individuals, age and sex structure of subadults, and osteobiography of two individuals. Although the inferences made should be taken with caution due to the fragmentary nature of the analyzed remains, it is concluded that the remains have an important potential as a source of knowledge of postdepositional factors, demography and living conditions of the high socio-economic status population of the city of Montevideo in the second half of the 19th century and first half of the 20th century.

En enero de 2019 se produjo un colapso parcial del ala «E» del primer cuerpo de nichos funerarios del cementerio Central de Montevideo, que afectó 64 nichos que contenían inhumaciones desde mediados del siglo XIX hasta el presente. El trabajo arqueológico de rescate del sector derrumbado resultó en la recuperación de estructuras funerarias intactas o poco alteradas y en la extracción de restos desplazados o aislados que fueron analizados en forma separada y son el objeto de este trabajo. Se estudiaron los restos con la finalidad de determinar número de individuos, estructura sexual y etaria, y el efecto del derrumbe y la metodología de recuperación en la representación de elementos óseos. Asimismo, se realizaron tres estudios puntuales sobre subconjuntos de la muestra: tafonomía de individuos adultos, estructura etaria y sexual de los subadultos, y osteobiografía de dos individuos. Si bien la fragmentariedad de los restos abordados implica que las inferencias realizadas deben tomarse con precaución, se concluye que los restos tienen un potencial importante como fuente de conocimiento de factores postdepositacionales, demografía y condiciones de vida de la población de estatus socioeconómico alto de la ciudad de Montevideo de la segunda mitad del siglo XIX y primera mitad del siglo XX.
Analysis of bone remains recovered in the archaeological rescue of the central cemetery (Montevideo,Uruguay)
Keywords: bioarchaeology; historical cemeteries; taphonomy; demography; osteobiography; Bioarqueología; Cementerios históricos; Tafonomía; Demografía; Osteobiografía; https://purl.org/pe-repo/ocde/ford#6.01.02